Surgery's role in contemporary osteoarticular infection management - De Marco, Giacomo; Vazquez, Oscar; Gavira, Nathaly; Ramadani, Ardian; Steiger, Christina; Dayer, Romain; Ceroni, Dimitri (Frontiers in Pediatrics, 2022)
The treatment paradigm for osteoarticular infections (OAIs) has changed drastically over the past 80 years, from the advent of penicillin to the use of broad-spectrum antibiotics. Before these drugs, surgery was the only available treatment for OAIs; today, antibiotic therapy is considered the primary response to them. As a result, surgical treatment of OAIs is thus far more rarely indicated, sometimes even considered outdated and obsolete. However, long experience has taught us that many OAI contexts can still benefit from surgical management, constituting an essential complement to medical treatment. The present article seeks to contextualize this discussion by providing a chronological review of the surgical treatments used in cases of OAI and describing the quality of evidence supporting their rehabilitation in well-established situations.